2005
DOI: 10.1108/02610150510788088
|View full text |Cite
|
Sign up to set email alerts
|

The status of women revisited: the case of Nepal

Abstract: This article offers a new perspective on assessing the status of women. It focuses on female endangerment and inequality among women as new dimensions of development and change. The article examines concepts of gender inequality and empowerment offered by the United Nations Development Programme (UNDP). The case of Nepal is discussed becasue of its serious neglect and deprivation of women. It is argued that while gender gaps matter, disparities among women are equally important constraining the country’s prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This is compounded by the 'masculine' nature of Nepal where it is challenging for women to gain political status and the religious trends tend to place dominance heavily with the male population. Chetterjea and Basu (1978)and Phillips et al (2009) find that countries with a large social distance manifest more issues of integration between men and women; Hosni and Lundberg (2005) note that there are severe issues of integration between men and women in Nepal. In the case of Nepali tea houses, where the obstacle of men within a deep hierarchy is removed, the potential for faster, more successful empowerment politically, socially and professionally is evident.…”
Section: Definition Of Empowermentmentioning
confidence: 99%
“…This is compounded by the 'masculine' nature of Nepal where it is challenging for women to gain political status and the religious trends tend to place dominance heavily with the male population. Chetterjea and Basu (1978)and Phillips et al (2009) find that countries with a large social distance manifest more issues of integration between men and women; Hosni and Lundberg (2005) note that there are severe issues of integration between men and women in Nepal. In the case of Nepali tea houses, where the obstacle of men within a deep hierarchy is removed, the potential for faster, more successful empowerment politically, socially and professionally is evident.…”
Section: Definition Of Empowermentmentioning
confidence: 99%
“…Chetterjea andBasu (1978), andPhillips, Rothbard andDumas (2009) find that nations with such considerable social disparity have larger gaps between the rights and capacities of males and females. Hosni and Lundberg (2005) state that there continue to be strict parameters defining the social distances between males and females in Nepal. In order to better understand, document and counteract the embedded patriarchy and gender reproductions that position Nepali women as inferior, incapable and irrelevant to economic growth, our research explored women's lived experiences in Nepal, and the effects and effectiveness of Nepali women's interventions within their own lives that enhance women's rights, power and agency.…”
Section: Entrepreneurship To Disrupt Patriarchal Hegemonymentioning
confidence: 99%
“…This is compounded by the 'masculine' nature of Nepal where it is challenging for women to gain political status and the religious trends tend to place dominance heavily with the male population. Chetterjea and Basu (1978) Phillips, Rothbard, and Dumas (2009) find that countries with a large social distance manifest more issues of integration between men and women; Hosni and Lundberg (2005) note that there are severe issues of integration between men and women in Nepal. In the case of Nepali Tea Houses, where the obstacle of men within a deep hierarchy is removed, the potential for faster, more successful empowerment politically, socially and professionally is evident.…”
Section: Introductionmentioning
confidence: 99%
“…Chetterjea and Basu (1978) and Phillips et al (2009) found that countries with a large social distance manifest more issues of integration between men and women. Hosni and Lundberg (2005) note that there are severe issues of integration between men and women in Nepal. In the case of Nepali tea houses, where the obstacle of men within a deep hierarchy is removed, the potential for faster, more successful empowerment politically, socially and professionally is evident.…”
Section: Introductionmentioning
confidence: 99%